Law : metaphysics, meaning, and objectivity - Villanueva, Enrique. (Rodopi Philosophical Studies, 2007)
Papers in philosophy of law by some of the younger cutting-edge contributors to the field. Two sets of issues of crucial current importance are taken up. The first part deals with issues of meaning and objectivity in the metaphysics of law. The second part is about rights theory. This volume will be required reading for anyone interested in philosophy of law, and also of use for those with broader interests in ethics, metaethics, and social and political philosophy.